2015
DOI: 10.1007/s11916-015-0498-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving Medication Adherence in Migraine Treatment

Abstract: Medication adherence is integral to successful treatment of migraine and other headache. The existing literature examining medication adherence in migraine is small, and the methodologies used to assess adherence are limited. However, these studies broadly suggest poor adherence to both acute and preventive migraine medications, with studies using more objective monitoring reporting lower adherence rates. Methods for improving medication adherence are described, including organizational strategies, provider-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 32 publications
(34 reference statements)
3
36
1
Order By: Relevance
“…Adherence with preventive headache medications has predominantly been studied in migraine and adherence to migraine preventives has been found to decline over time ranging from 41 to 95% at 2 months and decreasing to 21 to 80% at 6 months . One recent study using claims data to measure adherence found that amitriptyline had poorer odds of adherence compared to topiramate, the most commonly prescribed medication in their sample . In patients using amitriptyline, adverse events have been cited as the most common reason for stopping .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adherence with preventive headache medications has predominantly been studied in migraine and adherence to migraine preventives has been found to decline over time ranging from 41 to 95% at 2 months and decreasing to 21 to 80% at 6 months . One recent study using claims data to measure adherence found that amitriptyline had poorer odds of adherence compared to topiramate, the most commonly prescribed medication in their sample . In patients using amitriptyline, adverse events have been cited as the most common reason for stopping .…”
Section: Discussionmentioning
confidence: 99%
“…Non‐adherence is a problem in many diseases and is multifactorial, related to patient characteristics, medication complexity, the disease being treated, and the method of treatment . A recent review discussing medication adherence in migraine headache prophylaxis provided a few strategies .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even an appropriate prescription will fail to help the patient if he does not use the medication adequately. Common examples include the early intake of acute medications and the sufficient duration of a prophylaxis trial . Adequate medications may also fail to help a patient if significant lifestyle issues contributing to migraine frequency are not addressed or if overuse is not managed .…”
mentioning
confidence: 99%